Analisis Kualitas Bahasa pada Teks Berita di Website Koran Tempo Edisi Februari 2024 sebagai Kelayakan Bahan Ajar Membaca Kritis bagi Mahasiswa - Efriza Kharidatul Bahiyah; Eva Annisa Riska; Ricky Febianto; Fahmi Nur Hidayana; Himah Az Zahra; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Currently, there are many platforms used by writers to publish news, one of which is through mass media. In publishing news, a writer must pay attention to good and correct language quality in order to meet the requirements of linguistic quality. Thus, there needs to be more understanding from a writer in order to write spelling correctly and correctly according to writing guidelines. The purpose of this research is to check the correctness of news text writing has fulfilled the rules of good and correct language and in accordance with the user situation in a mass media. If a mass media does not present news text writing using good and correct language rules, its competence needs to be doubted. The approach used in this research is a syntactic approach using a qualitative descriptive method. This method is used to investigate and explain things related to a reality that occurs in the surrounding environment. The results of the analysis and discussion of the research prove that in the news text on the February 2024 edition of Koran Tempo website there are still errors in word writing, errors in the use of punctuation marks, and errors in the use of letters. The quality of language in the news text is classified as good if it meets the requirements of no errors in writing words, punctuation, letters, and spelling. With this research, it is hoped that it can increase knowledge about language and can improve the ability to read news texts, analyze language quality, and provide guidance to writers to pay attention to linguistic rules or use standard language in writing so that it is easily understood by the public.